A Descriptive Study to Assess the Level of Compassion Fatigue among Nurses Working in Dr. L. H. Hiranandani Hospital - Thomas, Elizebeth; Valsa Thomas, Capt.; Susan Varghese, Soniya (International Journal of Nursing Research, 2023)
Aim: The study aimed to identify the level of compassion fatigue among the nurses and to correlate the level of compassion fatigue with demographic variables. Materials and Methods: The study was conducted on 200 staff nurses working in Dr. L. H. Hiranandani Hospital. The design used for the study is descriptive research design. Samples selected using non-probability convenient sampling technique. Tool used for the study is structured questionnaire. Results: Nurse creates a healing environment for patients and relatives with their daily interaction and technical skills. Primary task as helping professional is to meet the physical and emotional needs of the patient. Although compassion fatigue is a treatable problem, it causes severe negative effect on nurse’s professional as well as personal life. To prevent this, we need to understand the early signs and symptoms of compassion fatigue. Compassion fatigue remains significant concerns in nursing, affecting both individuals and organizations. There are many strategies to prevent themselves from compassion fatigue. Compassion fatigue plays an important role in the professional outcome of the nurses. The data collected from staff nurses working in Dr. L. H. Hiranandani Hospital show average level of compassion fatigue for majority of the nurses 84% have average level of compassion fatigue and 16% of nurses show high level of compassion fatigue. Conclusion: The prevention of compassion fatigue starts from self-care. However, most of the nurses put their needs at last. Organizations should provide a supportive work environment, good opportunities, and guidelines for the nurses to work efficiently.